The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1124/mol.61.4.786
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Differentially Affects Basal and Lipopolysaccharide-Induced sPLA2-IIA Expression in Alveolar Macrophages through NF-κB and PPAR-γ–Dependent Pathways

Abstract: Secretory type IIA phospholipase A 2 (sPLA 2 -IIA) is a critical enzyme involved in inflammatory diseases. We have previously identified alveolar macrophages (AMs) as the major pulmonary source of lipopolysaccharide (LPS)-induced sPLA 2 -IIA expression in a guinea pig model of acute lung injury (ALI). Here, we examined the role of arachidonic acid (AA) in the regulation of basal and LPS-induced sPLA 2 -IIA expression in AMs. We showed that both AA and its nonmetabolizable analog, 5,8,11,14-eicosatetraynoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 43 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…EL provides an alternative pathway for FFA production, which is further incorporated into cells and then activates PPARa (41,42). Released arachidonic or linoleic acid can be the agonist for the PPAR/ retinoid X receptor heterodimer in macrophages (43). Moreover, the cholesterol accumulation in cells elicits its conversion to oxysterol, which is a potent endogenous activator for LXR and downstream PPAR and retinoid X receptor (44).…”
Section: Discussionmentioning
confidence: 99%
“…EL provides an alternative pathway for FFA production, which is further incorporated into cells and then activates PPARa (41,42). Released arachidonic or linoleic acid can be the agonist for the PPAR/ retinoid X receptor heterodimer in macrophages (43). Moreover, the cholesterol accumulation in cells elicits its conversion to oxysterol, which is a potent endogenous activator for LXR and downstream PPAR and retinoid X receptor (44).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift assay Nuclear proteins were extracted from 2610 6 cells as described previously [27]. The double-stranded oligonucleotide containing a Sp1 binding site consensus sequence (59-attcgatcggggcggggcgagc-39) was labelled with [c- ) and purified using a ProbeQuant G-50 micro column (GE Healthcare).…”
Section: Rt-pcrmentioning
confidence: 99%
“…It is well known that LPS and other inflammatory cytokines upregulate the transcription of sPLA 2 -IIA and its protein level in a variety of cells including macrophage [23], fibroblast [24], endothelial cells [25], and astrocytes [15]. Analysis of the expression level of sPLA 2 -IIA by primary HUVECs in response to varying concentrations of LPS for 24 h indicated that the induction level reaches plateau in cell culture supernatants at 100 ng/mL LPS (data not shown).…”
Section: Effect Of Fx or Fxa On The Expression And Activity Of Spla 2mentioning
confidence: 99%